Annealing Effect After RF (Radio Frequency) Sintering of Dental Zirconia Block with Dramatically Reduced Sintering Time: Experimental Study - Eun-Sung Choi; Je-Hoon Lee; Jung-Hyun Park; Ji-Hwan Kim (Applied Sciences)
Objectives: Radio frequency (RF) induction sintering has demonstrated superior performance compared to conventional sintering methods in previous studies. Furthermore, the annealing process is expected to further enhance the mechanical properties of sintered zirconia. This study aimed to investigate the effects of annealing on RF-sintered zirconia and provide empirical evidence supporting its role in optimizing sintering outcomes. Methods: A custom-built RF induction sintering furnace was utilized to process zirconia specimens under various annealing conditions (temperature range, annealing time). The sintered specimens underwent three-point flexural strength testing, followed by microstructural analysis using scanning electron microscopy (SEM). Statistical analysis was performed using one-way ANOVA and Tukey’s post hoc tests to assess the significance of differences between groups. Results: The optimal sintering temperature for RF induction sintering was determined to be 1350 °C, with a minimum annealing duration of 20 min at 1220 °C. Notably, even in the absence of annealing, RF sintering at 1350 °C for 20 min produced specimens with higher flexural strength than those obtained through conventional sintering methods. However, due to variability in mechanical properties, the incorporation of annealing is recommended for clinical applications to ensure consistency and reliability. Conclusions: RF induction sintering significantly reduced both energy consumption and processing time compared to conventional sintering techniques, particularly when combined with annealing. While full densification could be achieved within 20 min without annealing, a total processing time of 30 min, including annealing, was found to enhance process stability and ensure reliable mechanical properties. These findings suggest that both sintering and annealing are critical for achieving optimal densification in zirconia, with annealing playing a key role in improving consistency and reproducibility.